ANTI-INFLAMMATORY AND ACUTE TOXICITY EVALUATION OF AQUEOUS INFUSION EXTRACT OBTAINED FROM AERIAL PARTS OF MARRUBIUM DESERTI DE NOÉ GROWING IN ALGERIA - Saad, Somia; Ouafi, Saida; Chabane, Djamila (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Marrubium deserti de Noé, which is locally known as “Merriouet saharaui”, is widely used in Algeria as a traditional treatment ofmany ailments. In this study, the anti-inflammatory and acute toxicity of the aqueous infusion extract from aerial parts of Marrubium desertiwere investigated. Meanwhile, acute oral toxicity of M. deserti, as well as its anti-inflammatory activity is reported for the first time.Materials and Method: The anti-inflammatory activity was evaluated using carrageenin-induced paw oedema in mice at three different doses(250, 500 and 1000mg/kg body weight. Data were analyzed by one-way ANOVA followed by Dunnett’s t-test.Results: The aqueous infusion extract (250, 500 and 1000mg/kg body weight, orally administered, n=6) showed a significant (P<0.05) inhibitionof carrageenin-induced mice paw oedema by 11.22, 20.73 and 44.03% respectively in the third hour when compared to the control group.Acetylsalicylic acid (ASA, 50mg/kg) as the positive control showed 32.08% inhibition. The oral LD50 values in mice were found to be greaterthan 2000mg/kg. The relatively high oral median lethal dose (>2000mg/kg) suggests that the aqueous infusion extract has a relatively low acutetoxicity when taken orally for a single dose.Conclusions: The present study indicates that M. deserti has a significant anti-inflammatory effect and confirms its traditional use as a treatmentof pain, yet it suggests further investigations to be carried out to determine the active chemical constituents.